2012
DOI: 10.1186/1478-811x-10-33
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR4/NADPH oxidase/ROS-activated p38 MAPK in VCAM-1 expression induced by lipopolysaccharide in human renal mesangial cells

Abstract: BackgroundIn bacteria-induced glomerulonephritis, Toll-like receptor 4 (TLR4) activation by lipopolysaccharide (LPS, a key component of the outer membranes of Gram-negative bacteria) can increase oxidative stress and the expression of vascular cell adhesion molecule-1 (VCAM-1), which recruits leukocytes to the glomerular mesangium. However, the mechanisms underlying VCAM-1 expression induced by LPS are still unclear in human renal mesangial cells (HRMCs).ResultsWe demonstrated that LPS induced VCAM-1 mRNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 45 publications
4
76
0
Order By: Relevance
“…These factors have important functions in the regulation of the inflammatory and proliferative responses in VSMCs, which are a major component of blood vessels (Chistiakov et al 2015). In addition, VSMCs showed increased proliferation and production of fibronectin owing to AGEs-induced inflammatory cytokine production (Kume et al 2000;Sakata et al 2000;Lee et al 2012). In our experiments, glycol-AGEs were found to increase the expressions of RAGE, MCP-1, IL-6, and PAI-1 in VSMCs for 24 h when cells were cocultured with HUVECs and THP-1 cells ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…These factors have important functions in the regulation of the inflammatory and proliferative responses in VSMCs, which are a major component of blood vessels (Chistiakov et al 2015). In addition, VSMCs showed increased proliferation and production of fibronectin owing to AGEs-induced inflammatory cytokine production (Kume et al 2000;Sakata et al 2000;Lee et al 2012). In our experiments, glycol-AGEs were found to increase the expressions of RAGE, MCP-1, IL-6, and PAI-1 in VSMCs for 24 h when cells were cocultured with HUVECs and THP-1 cells ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are important intracellular signalings and play critical roles in regulating inflammatory responses (12). LPS has been shown to mediate p42/p44 MAPK, p38 MAPK, and JNK1/2 activation (10,29). Moreover, p42/p44 MAPK has been shown to participate in the regulation of a large variety of processes, including cell adhesion, cell migration, cell survival, differentiation, metabolism, proliferation, and transcription (26).…”
Section: Discussionmentioning
confidence: 99%
“…c-Src has been shown to regulate ICAM-1 expression in various cell types (9,16). In addition, LPS can mediate c-Src activation and then cause the inflammatory responses (7,10). Previous studies indicated that c-Src regulates platelet-derived growth factor receptor (PDGFR) and epidermal growth factor receptor (EGFR) transactivation (13), which further promotes inflammatory responses.…”
mentioning
confidence: 99%
“…Immunoprecipitation assay was performed as described previously (43). HUVEC lysates or kidney lysates of C57BL/6 mice containing 200 mg of total protein were incubated with rabbit anti-CAV-1 (Abcam; 1/100 v/w) or rabbit IgG (Santa Cruz Biotechnology) for 2 h at 4˚C on a rotating device, followed by the addition of Protein A-G PLUS Agarose (Santa Cruz Biotechnology) overnight under the same conditions.…”
Section: Immunoprecipitation Assaymentioning
confidence: 99%